As a Matter of Size: The Importance of Critical Mass and the Consequences of Scarcity for Television Markets - Christian Edelvold Berg (Copenhagen Business School (CBS), 2013)
This thesis “As a matter of size” demonstrates that size does indeed matter. Television markets have common characteristics across small and large markets, but the implications of these characteristics are varied due to the difference in size of economy and population. The influence of variable size is a consequence of the economic conditions of scarcity (limited resources) and thus the relative critical mass of the media market. Thus, the influence of size is an expression of the television market's inability to operate on normal market terms for provisioning particular types of services. Larger markets (measured by economy and population) have a higher potential of securing such content commercially. But all markets suffer from challenges in securing provisioning of original domestic content. Market intervention and public subsidy play an important role when it comes to securing domestic production. Political intervention can to some extent counteract the effects of the common characteristics, by changing market conditions through political regulation or subsidisation. The thesis shows that the European television markets mainly operate under conditions of oligopoly, usually in the form of different types of duopolies. The effect of size on market concentration is not as unambiguous as estimated in the literature, as the scope and extent of market intervention influence this quite intensely. Moreover, the study shows that television markets are dominated by relatively few, usually local, media companies and the multinational companies in most markets currently do not pose a real danger - but there are signs of a development which requires further research. Public service companies remain relatively strong in the markets studied, and continue to play an important role as a counterweight to national and international commercial competitors. Different markets require different policies that take into account the conditions in that specific market, in order to achieve a certain desirable merited effect. The thesis supports the view that a "one size fits all" policy across several markets when it comes to media regulation, risks not yielding the warranted results. Markets with different conditions, exposed to the same type of regulation, might have overall positive effects, but could also easily have a very negative impact if the conditions in a particular market do not fit with the intent of the policy. It is therefore far from certain that a "one size fits all" regulation will have the intended uniform effect on the affected market across several markets. This is especially true for markets that are challenged by having both a small population and a small economy. In a sense it is a paradox that the interest at European level in fair competition and equal opportunity for success can lead to different conditions of competition in a domestic market, as players may be subject to various conditions (in a way it can also be regarded as a consequence of domestic policy interventions), where the domestic players can face a strong international player, and as a result of the internal market and the Audiovisual Media Services directive, can achieve a competitive advantage, for example in relation to choosing the most lenient advertising rules. The analytical work of the thesis can substantiate claims that size has a significant effect and that there are concrete policy implications depending on size of economy and population, due to scarcity of resources in the individual market.
hdl:10398/8629
Keywords: 650